Group III nitride semiconductor nanoparticles

JP7629702B2Active Publication Date: 2025-02-14STANLEY ELECTRIC CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020164727
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2025-02-14
Estimated Expiration
2040-09-30

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、III族窒化物ナノ粒子において、ウルツ鉱構造と閃亜鉛鉱構造の2つの結晶構造を一つの粒子内に混在させることで結晶の非対称性を緩和させることができる。これにより、正の電荷を持つIII族元素と負の電荷を持つ窒素元素の分極のバランスを安定化させることができ、ウルツ鉱構造特有のピエゾ電界を抑制することができ、発光効率の低下を防ぐことができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007629702000001
    Figure 0007629702000001
  • Figure 0007629702000002
    Figure 0007629702000002
  • Figure 0007629702000003
    Figure 0007629702000003
Patent Text Reader

Abstract

To provide Group III nitride nanoparticles having good luminous efficiency by suppressing a piezoelectric electric field caused by strain received by the Group III nitride nanoparticles.SOLUTION: Group III nitride nanoparticles represented by AlxGayInzN(0≤x,y,z≤1) comprise two crystal structures of a wurtzite structure and a sphalerite structure in one particle. Alternatively, Group III nitride nanoparticles comprise a core-shell structure with a core and a shell, in which particles constituting the core comprise two crystal structures of a wurtzite structure and a sphalerite structure in the particles. The nanoparticles containing the two crystal structures can be produced by using a solvent containing a phosphorus-containing solvent as a reaction solvent, and the mixing ratio between the two crystal structures is wurtzite structure: sphalerite structure=20:80 or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nanoparticles of Group III nitrides such as Al, Ga, and In, and in particular to nitride semiconductor nanoparticles that suppress a decrease in luminous efficiency due to a piezoelectric field.

[0002] Group III nitride semiconductor nanoparticles (hereinafter simply referred to as group III nitride nanoparticles) are a material that is expected to be applied to EL devices such as lighting and displays, light-receiving elements such as sensors and solar cells, and photocatalysts for hydrogen generation, etc.

[0003] It is known that the main crystal structures of III-nitrides are the wurtzite structure (hexagonal crystal) and zinc blende structure (cubic crystal). Of these, nanoparticles with the wurtzite structure have asymmetric crystals, so when stress is applied to the crystal and it becomes distorted, the balance of polarization between the positively charged III-group elements and the negatively charged nitrogen elements is lost, which causes an electric field (piezoelectric field) in the C-axis direction. When a piezoelectric field is generated, the energy band of the III-nitride semiconductor nanoparticles is bent, and the degree of overlap between the wave functions of electrons and holes becomes smaller, decreasing the probability of luminescence recombination. This reduces the luminous efficiency.

[0004] In contrast, Group III nitrides with a zinc-blende structure do not have the problem of piezoelectric fields caused by the above-mentioned crystal asymmetry, but the zinc-blende structure is a metastable structure in Group III nitrides, and it is difficult to obtain it stably like the wurtzite structure, which is a stable phase. For example, Patent Document 1 discloses Group III nitride nanoparticles and a manufacturing method thereof, and only states that a cubic crystal (zinc-blende structure) was obtained for some InN cores.

[0005] Furthermore, in the case of nanoparticles, if the particle shape is anisotropic, internal stress is generated in the particle, which leads to a decrease in the luminous efficiency due to the piezoelectric field.

[0006] Furthermore, when the III-nitride nanoparticles are used for the above-mentioned applications, for example as nanoparticle phosphors, in order to improve the luminous efficiency, a core-shell structure in which the core particles are covered with a shell is required, but this structure may cause a decrease in luminous efficiency. Specifically, due to the difference in lattice constant between the core and the shell, and the difference in the constituent materials and their ratios, internal stress is generated in the particles, and the efficiency decrease is even greater in the case of a core-shell structure than in the case of a single core. Furthermore, when the shape of the core-shell particles is anisotropic, such as a rod shape or a disk shape, the core is subjected to stress due to the shape anisotropy, which leads to a decrease in luminous efficiency due to the piezoelectric field. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 5847863 Summary of the Invention [Problem to be solved by the invention]

[0008] The problem of the generation of piezoelectric fields due to differences in the shape, lattice constant, and composition of the particles or core-shell structures described above, combined with the wurtzite crystal structure, reduces the luminescence efficiency of III-nitride nanoparticles.

[0009] An object of the present invention is to solve the problem of reduction in luminous efficiency of Group III nitride nanoparticles caused by a piezoelectric field, and to provide Group III nitride nanoparticles in which the reduction in luminous efficiency is suppressed even in the case of particles having a distorted structure. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides Group III nitride nanoparticles in which two crystal structures, a wurtzite structure and a zinc blende structure, are mixed within one particle. The Group III nitride nanoparticles of the present invention also include particles having a single composition and a mixture of two crystal structures, and particles having a core-shell structure comprising a particle having a single composition and a mixture of two crystal structures as a core surrounded by a shell composed of a different composition from the core.

[0011] Here, the presence of two crystal structures in one particle means that in a group III nitride nanoparticle which is an aggregate of many particles, each particle has two crystal structures present in itself.

[0012] Furthermore, the method for producing Group III nitride nanoparticles of the present invention is a method for producing Group III nitride nanoparticles in which Group III nitride is synthesized by a thermal decomposition method using a Group III nitride raw material and a solvent, and is characterized in that a solvent containing a phosphorus-containing solvent is used as the solvent. Effect of the Invention

[0013] According to the present invention, in group III nitride nanoparticles, the two crystal structures, the wurtzite structure and the zinc blende structure, are mixed in one particle, thereby alleviating the crystal asymmetry. This stabilizes the polarization balance between the positively charged group III element and the negatively charged nitrogen element, suppresses the piezoelectric field specific to the wurtzite structure, and prevents a decrease in luminous efficiency.

[0014] Furthermore, since a piezoelectric field is an electric field that is generated when Group III nitride nanoparticles are strained in the in-plane direction of their growth surface, applying the present invention to Group III nitride nanoparticles that have factors (shape, composition) that increase the strain can have a significant effect, and also increases the freedom in designing III nitride nanoparticles. [Brief description of the drawings]

[0015] [Figure 1] Figure 1 shows the X-ray diffraction pattern of the wurtzite structure. [Diagram 2]FIG. 1 shows examples of shapes that the Group III nitride nanoparticles of the present invention can have: (A) an ellipsoidal particle, (B) a spherical core-shell particle, (C) a rod-shaped core-shell particle, and (D) a disk-shaped core-shell particle. [Diagram 3] FIG. 2 is a diagram showing the relationship between the composition of group III nitride nanoparticles and the energy gap and lattice constant. [Figure 4] FIG. 2 shows an X-ray diffraction pattern of the Group III nitride nanoparticles of Example 1. [Diagram 5] FIG. 2 is a graph showing the relationship between the crystal structure mixing ratio and the luminance of the Group III nitride nanoparticles of Examples 1 to 3 and the Comparative Example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the Group III nitride nanoparticles and the method for producing the same of the present invention will be described. The group III nitride nanoparticles of the present invention are In x Ga y Al z These nanoparticles are expressed as N (0≦x, y, z ≦ 1), and contain a mixture of two crystal structures, wurtzite and zinc blende, within one particle. The mixture of two crystal structures within one particle makes it difficult for distortion to occur even under various conditions, such as composition and shape, that would distort the hexagonal lattice, resulting in high luminous efficiency. The mixture of two crystal structures within a particle can be calculated, for example, from precision structural analysis such as the Rietveld method, or the intensity ratio between (110) and (103) in the X-ray diffraction pattern.

[0017] The Rietveld method is a method for fitting the entire diffraction pattern using the least squares method to calculate quantitative values ​​such as lattice constants, and the mixture ratio can be calculated from the calculated lattice constant and the ratio of the lattice constant of the wurtzite structure to the lattice constant of the zinc blende structure. Measurements using the Rietveld method were performed using Bruker's crystal structure analysis software (TOPAS).

[0018] As shown in Figure 1, the X-ray diffraction pattern of the wurtzite structure shows that the (103) peak, which is not present in cubic crystals, appears in a position that is easily distinguishable from the (110) peak. On the other hand, in cubic crystals, there is no (103) peak near the (110) peak. For this reason, the coexistence of two crystal structures within a single particle can be confirmed by observing only one particle with a TEM and calculating the intensity ratio of the (110) peak common to the wurtzite and zinc blende structures and the (103) peak specific to the wurtzite structure from the diffraction pattern.

[0019] Furthermore, by measuring the X-ray diffraction pattern for a large collection of Group III nitride nanoparticles of the present invention and calculating the ratio R of the intensity ratio X1 of the measurement target (mixed crystal structure) to the intensity ratio X0 of wurtzite (110) to (103), the proportion of zinc blende in the mixed system can be calculated, and the mixing ratio can be calculated. R = (X1 / X0) x 100 Mixture ratio = R:(100-R)

[0020] The ratio of the wurtzite structure is preferably 10% or more, more preferably 20% or more, and even more preferably 30% or more. With a wurtzite ratio of about 10%, it is not possible to obtain a luminescence brightness superior to that of nitride nanoparticles having a wurtzite structure alone. On the other hand, the ratio of the zinc blende structure is preferably 50% or less. By making the ratio of the zinc blende structure, which is a metastable phase, less than half, the crystal structure of the group III nitride nanoparticles can be kept stable.

[0021] The III-nitride nanoparticles of the present invention have two crystal structures mixed in the particle, so that the strain in the crystal growth direction can be suppressed, and the piezoelectric field generated when the particle is strained can be suppressed. There are two main factors that give strain to III-nitride nanoparticles. One is the shape of the nanoparticle. For example, in the case of a single particle, an elliptical spherical particle as shown in FIG. 2(A) is distorted due to its shape anisotropy. In the case of nanoparticles with a core-shell structure, as shown in FIG. 2(B), it is ideal to form a shell almost uniformly around a spherical core from the viewpoint of distortion, but depending on the combination of synthesis conditions and compositions, a rod shape as shown in (C) or a disk shape as shown in (D) is formed. These shape anisotropies cause distortion. The shape anisotropy referred to here is the value obtained by dividing the maximum diameter by the minimum diameter when the particle is observed by TEM, that is, the aspect ratio is 1.1 or more.

[0022] Another factor is the lattice mismatch between the core and shell that occurs when materials are combined in nanoparticles with a core-shell structure. In Type 1 quantum dots, the combination is such that the shell has a larger energy gap than the energy gap of the core particle. Figure 3 shows the relationship between the composition of III nitrides (bulk crystals) and the energy gap and lattice constant, and the lattice constants can be made equal if the composition combination is located on the line along the vertical axis in the figure. However, in this case, there is a limit to how large the energy gap difference can be. A certain degree of lattice mismatch is unavoidable in combinations that increase the energy gap difference.

[0023] The Group III nitride nanoparticles of the present invention have core particles that contain a well-symmetric zinc blende structure at a predetermined ratio within the particle, and therefore the distortion caused by these factors can be suppressed, thereby enabling the luminescence efficiency to be increased compared to particles having only the wurtzite structure.

[0024] The composition of the group III nitride nanoparticles is the same as that of conventional group III nitrides, and may be any binary nitride such as InN, GaN, or AlN. xGa y Al z N (wherein x, y, and z are each 0 or more and 1 or less, and x+y+z=1 is satisfied).

[0025] In the case of core-shell nanoparticles, which have a structure in which the core is covered with a shell, the above compositions are combined to provide a shell with a larger energy gap than the energy gap of the core particle. As shown in Figure 3, the higher the ratio of Al, the larger the energy gap, and the higher the ratio of In, the smaller the energy gap, with Ga being intermediate between these two. Therefore, it is preferable to increase the ratio of Al or Ga as the shell material, and the core should have a composition that provides a lower energy gap than that.

[0026] In addition, the composition of the core and shell materials is adjusted taking into consideration the lattice matching between the two. As for lattice matching, a core-shell structure with good structural matching can be obtained by combining compositions with similar lattice constants in the graph shown in Figure 3. However, as described above, by mixing the crystal structure of the present invention, distortion due to lattice mismatch can be suppressed as described later, so that a relatively free combination of compositions is possible.

[0027] Next, an example of a method for producing Group III nitride nanoparticles according to the present invention will be described. The Group III nitride nanoparticles of the present invention can basically be produced by chemical synthesis using a conventional pyrolysis method, in which a Group III raw material and a nitrogen raw material are reacted at high temperature together with a specific solvent. However, in conventional chemical synthesis, tetradecylbenzene, 1-octadecene, trioctylphosphine, diphenyl ether, benzene, etc. are used as solvents, but in the present invention, it is preferable to use a phosphorus-containing solvent in order to mix two crystal structures within the particles. As the phosphorus-containing solvent, trioctylphosphine (TOP), trioctylphosphine oxide, etc. can be used, and TOP is particularly suitable.

[0028] The solvent may be 100% phosphorus-containing solvent, or a mixed solvent with the above-mentioned general synthetic solvent may be used. However, the higher the ratio of phosphorus-containing solvent in the solvent used in the reaction, the higher the ratio of zinc blende structure can be. The solvent may be 100% phosphorus-containing solvent, in which case the ratio of zinc blende structure can be increased to nearly 40%.

[0029] When a group III raw material and a nitrogen raw material are synthesized into a group III nitride through a chemical reaction, a precursor is formed first, and then goes through the processes of nucleation and crystal growth to become crystal particles. However, the presence of phosphorus, which is in the same group V as nitrogen, in the reaction system at the time of precursor formation changes the covalent bond nature of the III-V bond, which in turn changes the interatomic distance, and is thought to result in the partial production of a zinc blende structure.

[0030] Other than that, conventional manufacturing methods can be adopted. For example, the raw material is first heated to about 140 to 150°C at a predetermined heating rate and reacted for a predetermined time to form a precursor. Then, the temperature is raised to a higher temperature, for example, about 300 to 400°C, and the reaction is allowed to proceed to grow crystals. By controlling this reaction time, the particle size of the nanoparticles produced can be controlled.

[0031] After the particles are generated, the nanoparticles are collected by centrifugation and centrifugal washing using a solvent such as ethanol. If necessary, a treatment for imparting dispersibility to the nanoparticles may be performed.

[0032] In the case of a core-shell structure, a phosphorus-containing solvent is used to produce core particles having a mixed crystal structure within the particle, and then the core particles, shell raw materials, and solvent are used to synthesize in the same manner as the core particles. The above-mentioned general reaction solvents can be used as the solvent for synthesizing the shell. This makes it possible to obtain nitride nanoparticles having a core-shell structure in which the shell covers the periphery of the core particles having a mixed crystal structure within the particle.

[0033] As the group III raw material, materials used in general chemical synthesis, for example, group III halides such as indium iodide, can be used. Organic materials such as trimethylates and triethylates can also be used. As the nitrogen material, ammonia, metal azide compounds, metal nitrides, amines, metal amides, etc. can be used. In particular, metal amides such as sodium amide and lithium amide are preferred.

[0034] The amount of Group III raw material used for the core and shell is determined by the stoichiometric amount, so it is sufficient to use the amount of Group III raw material that will result in the designed composition, and by using an equivalent or greater amount of nitrogen raw material, a Group III nitride with a target composition can be obtained. In addition, by using an excess amount of nitrogen (V) raw material (for example, VV / III=40) and setting the reaction temperature to a high temperature of about 400°C, the shape of the core particle can be made elliptical. In addition, for the shell, the shape of the core-shell type particle can be controlled by using an excess amount of nitrogen raw material (for example, V / III=40) or setting the reaction temperature (during precursor formation or crystal growth) to a high temperature of about 400°C, and rod-shaped or disk-shaped particles can be obtained. EXAMPLES

[0035] Examples of the method for synthesizing Group III nitride semiconductor nanoparticles of the present invention will now be described. In the following examples, a Parr 4740 synthesis vessel and an MS-ESB (As One) heating device were used. This is a combination of a mantle heater and a stirrer. Synthesis was carried out in a glove box where the oxygen and moisture concentrations were controlled to 1 ppm or less, by putting the solvent and raw materials into a platinum inner cylinder with a lid, and then placing this in the synthesis vessel.

[0036] In addition, the crystal structure analysis in each embodiment, particularly the mixture ratio of the zinc blende structure and the wurtzite structure, was calculated from quantification by precision structure analysis such as Rietveld analysis and the intensity ratio of (110) and (103) by XRD.

[0037] <Example 1> (InGaN particles) Indium iodide (Aldrich, 99.998%) was used as the indium source, 53.5 mg (0.0.108 mmol), gallium iodide (Aldrich, 99.99%) was used as the gallium source, 194.6 mg (0.0.432 mmol), lithium amide (Aldrich, 97%) was used as the nitrogen source, and 6 ml of trioctylphosphine (TOP) (Sigma Aldrich, 97%) was used as the solvent.

[0038] The raw materials and the solvent were filled in the inner cylinder, and the inner cylinder was placed in the synthesis vessel. The synthesis vessel was then set on a mantle heater and heated to 150°C at a heating rate of 5°C / min. A solid phase precursor was formed by reacting for 5 minutes at a temperature between 140°C and 160°C. At this time, stirring was performed with a stirrer in order to react lithium amide, which has low solubility in the solvent, uniformly. The stirring speed was 600 rpm. The synthesis vessel was then heated to 400°C and synthesis was performed for 1 hour. After synthesis, the vessel was cooled with cold water in order to quickly stop the reaction.

[0039] After the synthesis was completed, ethanol was added to the synthesis solution and centrifuged by ultracentrifugation. After removing the supernatant after centrifugation, ethanol was added again and centrifuged. After this process was repeated three times, hexane was added and centrifuged again, and finally the particles were centrifuged and washed with ethanol to recover the particles. The centrifugation conditions were 28,000 rpm x 30 min.

[0040] The collected particles were measured by XRD, XRF, and TEM to evaluate the crystal structure, particle size, and the like. FIG. 4 shows the XRD diffraction pattern of the particles of Example 1. FIG. 4 also shows the peak positions of the X-ray diffraction patterns of the wurtzite structure and the zinc blende structure. From this diffraction pattern, it can be seen that the peak of the wurtzite structure is blunted and the peak of the zinc blende structure is clear. Furthermore, the mixture ratio of the wurtzite structure and the zinc blende structure was calculated using the intensity ratio of (110) and (103) of the XRD and quantification by precise structure analysis by the Rietveld method. As a result, the particles of Example 1 had a wurtzite structure:zinc blende structure=70:30.

[0041] <Examples 2 and 3, Comparative Example 1> The solvent charged into the reaction vessel (inner cylinder) was different from the solvent TOP used in Example 1 as follows, and nitride particles were synthesized and collected in the same manner as in Example 1. Comparative Example 1: DPE (diphenyl ether) Example 2: TDB (Tetradecylbenzene) Example 3: Mixture of DPE and TOP (DPE:TOP=1:1)

[0042] The XRD diffraction patterns of the particles of Comparative Example 1 and Example 2 are shown in FIG. 4, which shows the results of Example 1. As can be seen from FIG. 4, the crystal structure of the particles of Comparative Example 1 (solvent: DPE) was 100% wurtzite type. Example 2 (solvent: TDB) showed an intermediate pattern between Example 1 and Comparative Example 1. The mixture ratio of the wurtzite structure and zinc blende structure (wurtzite structure: zinc blende structure), calculated in the same manner as Example 1, was 90:10 for Example 2 and 80:20 for Example 3, and it was confirmed that both structures were mixed in both cases.

[0043] Furthermore, the luminance of Examples 1 to 3 and Comparative Example 1 was measured using a spectrofluorometer with an excitation wavelength of 365 nm. The results are shown in FIG. 5. As can be seen from this result, the mixture ratio and the luminance are almost proportional to each other, and the higher the ratio of the zinc blende structure, the higher the luminance. It can also be seen that the higher the ratio of TOP in the solvent, the higher the ratio of the zinc blende structure. Furthermore, in Example 2 using TDB as the solvent, the mixture of about 10% of the zinc blende structure was observed, but the luminance in this case was the same as in Comparative Example 1 using DPE, and it was confirmed that in the composition of this example, the luminance was improved when the ratio of the zinc blende structure was 10% or more. Note that the particles produced by the methods of Examples 1, 2, 3 and Comparative Example 1 had shape anisotropy.

[0044] <Example 4> (2.1 InGaN core / GaN shell) Indium iodide (Aldrich, 99.998%) was used as the indium source, 53.5 mg (0.108 mmol), gallium iodide (Aldrich, 99.99%) was used as the gallium source, 194.6 mg (0.432 mmol), lithium amide (Aldrich, 97%) was used as the nitrogen source, and 6 ml of trioctylphosphine (Sigma, Aldrich, 97%) was used as the solvent.

[0045] The raw materials and the solvent were filled into the inner cylinder, and the inner cylinder was then placed in the synthesis vessel. Synthesis was carried out under the same conditions as in Example 1, except that the synthesis temperature was 350° C. Centrifugation and centrifugal washing were then carried out, and the particles were recovered. The composition of the particles was In 0.2 Ga 0.8 The particle size was about 5 nm. Similarly to Example 1, the mixture ratio of the wurtzite structure and the zinc blende structure calculated from the XRD diffraction pattern was wurtzite structure: zinc blende structure=68:32.

[0046] Next, GaN shells were synthesized using the synthesized InGaN nanoparticles as core particles. The shell materials were 243.2 mg (0.540 mmol) of gallium iodide (99.99% by Aldrich) as the gallium source, 246.9 mg (10.80 mmol) of lithium amide (97% by Aldrich) as the nitrogen source, and 6 ml of diphenyl ether (99% by Sigma Aldrich) as the solvent.

[0047] The shell material and solvent, along with 25.0 mg (0.27 mmol) of InGaN core particles, were filled into the inner cylinder, and the inner cylinder was placed in the synthesis vessel. The synthesis vessel was set on a mantle heater, and the temperature was raised to 150°C at 5°C / min, and the reaction was carried out for 5 minutes at a temperature between 140°C and 160°C with a stirring speed of 600 rpm to form a solid phase precursor. The synthesis vessel was then heated to 350°C, and synthesis was carried out for 1 hour. After the synthesis, the vessel was cooled with cold water to quickly stop the reaction. After the synthesis was completed, the particles were collected by centrifugation and centrifugal washing with ethanol in the same manner as in Example 1. As a result, core-shell type particles with InGaN as the core and GaN as the shell were obtained.

[0048] <Example 5> (GaN core / AlGaN shell) Core-shell nitride nanoparticles were produced in the same manner as in Example 4, except that the core and shell compositions were varied.

[0049] The core material was prepared by using 243.2 mg (0.540 mmol) of gallium iodide (manufactured by Aldrich, 99.99%) as a gallium raw material and 246.9 mg (10.80 mmol) of lithium amide (manufactured by Aldrich, 97%) as a nitrogen raw material. As in Example 4, 6 ml of trioctylphosphine (manufactured by Sigma Aldrich, 97%) was used as a solvent, and synthesis was performed in the same manner as in Example 4, and GaN core particles were collected.

[0050] The mixture ratio of the wurtzite structure and zinc blende structure in the core particles was wurtzite structure: zinc blende structure=65:35.

[0051] Using 22.6 mg (0.27 mmol) of the GaN core particles, 110.1 mg (0.27 mmol) of aluminum iodide (manufactured by Aldrich, 99.999%) as the aluminum source, 121.6 mg (0.270 mmol) of gallium iodide (manufactured by Aldrich, 99.99%) as the gallium source, 246.9 mg (10.80 mmol) of lithium amide (manufactured by Aldrich, 97%) as the nitrogen source, and 6 ml of diphenyl ether (manufactured by Sigma Aldrich, 99%) as the solvent, Al was deposited on the GaN core particles in the same manner as in Example 4. 0.5 Ga 0.5 The N shell was formed and the particles were collected.

[0052] <Examples 6 and 7> Core-shell structured nitride nanoparticles were produced in the same manner as in Example 4, but with different shell compositions (Example 6: InGaN core / AlInN shell, Example 7: InGaN core / InGaN shell).

[0053] In Example 6, Al 0.8 In 0.2 To prepare the N shell, 176.1 mg (0.432 mmol) of aluminum iodide (Aldrich, 99.999%) was used as the aluminum source, 53.5 mg (0.108 mmol) of indium iodide (Aldrich, 99.998%) was used as the indium source, and 246.9 mg (10.80 mmol) of lithium amide (Aldrich, 97%) was used as the nitrogen source.

[0054] In Example 7, In 0.1 Ga 0.9 To prepare the N shell, 176.1 mg (0.054 mmol) of indium iodide (Aldrich, 99.998%) was used as the indium source, 53.5 mg (0.486 mmol) of gallium iodide (Aldrich, 99.99%) was used as the gallium source, and 246.9 mg (10.80 mmol) of lithium amide (Aldrich, 97%) was used as the nitrogen source.

[0055] In both examples, as in Example 4, 0.2 Ga 0.8 An InGaN core particle was synthesized, and 25.0 mg (0.270 mmol) of this InGaN core particle was loaded into an inner cylinder together with the above shell material and 6 ml of a solvent, diphenyl ether (Sigma Aldrich, 99%). The inner cylinder was then placed in a synthesis vessel, and a shell was synthesized under the same conditions as in Example 4, to obtain particles in which an AlInN shell (Example 6) or an InGaN shell (Example 7) was laminated on an InGaN core particle.

[0056] <Example 8> (Rod) InGaN core particles (In 0.2 Ga 0.8GaN shells were synthesized using 25.0 mg (0.27 mmol) of N core particles. The ratio of group III (Ga) and group V (nitrogen) used in the synthesis was varied to synthesize rod-shaped shells.

[0057] That is, 243.2 mg (0.540 mmol) of gallium iodide (manufactured by Aldrich, 99.99%) was used as the gallium raw material, and 987.6 mg (43.20 mmol) of lithium amide (manufactured by Aldrich, 97%) was used as the nitrogen raw material. As the solvent, 6 ml of diphenyl ether (manufactured by Sigma Aldrich, 99%) was used. After the synthesis was completed, centrifugation and centrifugal washing were carried out in the same manner as in Example 4, and the particles were recovered.

[0058] <Example 9> (Disc) Using InGaN core particles synthesized in the same manner as in Example 4, a disk-shaped shell was synthesized by controlling the shell synthesis temperature.

[0059] In this example, the core composition and shell composition were the same as in Example 4, and the synthesis temperature after the precursor formation during shell synthesis was raised to 400°C and synthesis was performed for 1 hour, whereas it was 350°C in Example 4. Other than that, in the same manner as in Example 4, core-shell particles in which a GaN shell was formed on an InGaN core particle were obtained.

[0060] From the above examples, it was confirmed that it is possible to produce group III nitride nanoparticles in which two crystal structures, the wurtzite structure and the zinc blende structure, are mixed within the particle. It was also confirmed that the particle shape can be controlled by controlling the ratio (V / III) of the group III raw material and the nitrogen raw material used in the synthesis and the reaction temperature, and that group III nitride nanoparticles in elliptical or rod shapes can be produced. [Explanation of symbols]

[0061] 10: Group III nitride nanoparticles, 1: core, 2: shell

Claims

1. Al x Ga y In z N (0≦x, y, z≦1), wherein each particle contains a mixture of two crystal structures, i.e., a wurtzite structure and a zinc-blende structure, and the proportion of the zinc-blende structure is 25% or more in terms of an XRD diffraction intensity ratio.

2. The Group III nitride semiconductor nanoparticles according to claim 1, wherein the Group III nitride nanoparticles are represented by Ga y In z N (0≦y, z≦1).

3. 3. A Group III nitride semiconductor nanoparticle, comprising a core-shell structured Group III nitride nanoparticle having a core and a shell, wherein the particles constituting the core are the Group III nitride nanoparticles according to claim 1 or 2.

4. 4. The Group III nitride semiconductor nanoparticle according to claim 3, wherein the core and the shell have different lattice constants.

5. 4. The Group III nitride semiconductor nanoparticles according to claim 3, characterized in that they have shape anisotropy.

6. 6. The Group III nitride semiconductor nanoparticles according to claim 5, which have any one of an elliptical, rod-like and disk-like shape.

7. 3. The Group III nitride semiconductor nanoparticles according to claim 1 or 2, wherein the particles having two crystal structures therein have a zinc blende structure in a ratio of 30% or more in terms of XRD diffraction intensity ratio.

8. 3. The Group III nitride semiconductor nanoparticles according to claim 1, which have shape anisotropy.

Citation Information

Patent Citations

  • Corner metal fitting of side trough

    JP1983047863A

  • Method of transforming crystal structure of group 13 element nitride, group 13 element nitride, and structure containing cubic nitride

    JP2004284851A

  • Gallium nitride-based crystalline compound, method for producing the same, crystalline compound, method for producing the same and method for producing lithium cyanamide

    JP2006111520A

  • Manufacturing method of semiconductor nanoparticle, and semiconductor nanoparticle, and fluorescent substance using the same

    JP2012246470A

  • Manufacturing of nitride nanoparticles

    JP2012515802A